Mendorong Peranan Orang Tua dalam Memaksimalkan dan Mendukung Perkembangan Anak pada Usia Dini - Marsahip Marsahip (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
The role of parents is an important factor in the process of child development. Parents play a role in ensuring that children are healthy and safe by providing facilities and infrastructure to develop social skills and character and media to instill social and cultural values ​​as early as possible. Parents provide affection, acceptance, appreciation, recognition, and direction or guidance to their children. The relationship between parents and children is very important for building trust in others and themselves. It can also help the child's social, emotional and cognitive development. Research shows that a warm, open and communicative parent-child relationship; having reasonable age limits; and communicating why children should not do something will increase self-confidence and achievement in school and society.